Woodfuel in Rwanda: Impact on Energy, Poverty, Environment and Policy Instruments analysis - Mazimpaka, Ernest (Center of Biomass & Renewable Energy, Diponegoro University, 2014)
Rwanda’s geographical and socio-economic situations have shaped the energy situation and limited access to modern fuels. Woodfuel is the main source of energy for households and its trade a source of income and jobs in rural areas. Currently 85.2% of households’ land holding is less than 1 ha, insufficient to grow food and fuelwood for a household of the average size of 5.5 persons. Without well documented reports of the individual impact of each deforestation factor, woodfuels have been most blamed. This paper investigates how the current woodfuel industry impacts on energy, poverty and forests and analyses the woodfuel policy instruments. Considering woodfuel consumption under an only environmental or energy perspective has resulted in a search for a narrowly environmental or energy solution. Both failed to solve the problem of forest depletion. Current regulations limit the benefits traditionally derived from woodfuel commoditisation leading to a negative attitude towards policy instruments. The processes involved in producing charcoal and using it as a cooking fuel is inefficient and resource intensive. The barriers to large dissemination of improved cooking stoves include availability, relatively low cost of woodfuels, lack of improved stove diversity on the local market and weak government policy in regard to the woodfuel industry. Policies aiming to substitute or reduce woodfuel consumption, have not achieved the desired results and their implementations have not unarguably reduced deforestation. The paper recommends the community-based woodfuel production as sustainable management approaches to mobilise community support for sustainable forestry management and woodfuel production.